2020
DOI: 10.3390/cancers12071852
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Cancer MicroRNA Therapeutic Delivery Strategies

Abstract: In the field of molecular oncology, microRNAs (miRNAs) and their role in regulating physiological processes and cancer pathogenesis have been a revolutionary discovery over the last decade. It is now considered that miRNA dysregulation influences critical molecular pathways involved in tumor progression, invasion, angiogenesis and metastasis in a wide range of cancer types. Hence, altering miRNA levels in cancer cells has promising potential as a therapeutic intervention, which is discussed in many oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
143
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(143 citation statements)
references
References 169 publications
(206 reference statements)
0
143
0
Order By: Relevance
“…MicroRNA is emerging as a next generation cancer treatment [41][42][43][44]. Studies showed that miR-1291 had anti-tumor effects in multiple cancers including renal cancer, esophagus cancer, pancreatic cancer, and prostate cancer [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA is emerging as a next generation cancer treatment [41][42][43][44]. Studies showed that miR-1291 had anti-tumor effects in multiple cancers including renal cancer, esophagus cancer, pancreatic cancer, and prostate cancer [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies regarding the role of CaSR and its downstream signaling pathways in HL-1 cells are required. Although the HAp-based vector used here has a low transfection efficiency, it has already been used as a gene delivery system in in vivo cancer research experiments [38]. Furthermore, this system might be useful for increasing the knowledge about cellular uptake mechanisms in heart cells, which are difficult to transfect.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs seem to have the potential for therapeutic use [ 554 , 555 , 556 ]. However, the first clinical trials did not live up to expectations.…”
Section: Challenges For the Use Of Mirnas In Clinical Oncologymentioning
confidence: 99%